1981
DOI: 10.1037/0022-006x.49.4.508
|View full text |Cite
|
Sign up to set email alerts
|

The social cognitive development of abused children.

Abstract: Previous research on the impact of parental abuse on child development has typically been skewed to the more seriously injured or most socially disadvantaged families. The few studies attending to psychological consequences of abuse have further been limited by a failure to control for potentially confounding intellectual or demographic factors and have been too general in approach to provide effective guidelines for differential diagnosis, treatment, or theory building. The present study compared the social c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
1
7

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(87 citation statements)
references
References 24 publications
4
75
1
7
Order By: Relevance
“…The study results show that in the MG there was a significant prevalence of harmful sociocognitive skills, such as the use of attributive styles that are based on reporting causes of events as external, in line with what has been observed in other studies (e.g., Barahal et al 1981). In other words, the children/youths that had been victims of maltreatment showed little confidence in the possibility that they could have an impact on their own experiences.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The study results show that in the MG there was a significant prevalence of harmful sociocognitive skills, such as the use of attributive styles that are based on reporting causes of events as external, in line with what has been observed in other studies (e.g., Barahal et al 1981). In other words, the children/youths that had been victims of maltreatment showed little confidence in the possibility that they could have an impact on their own experiences.…”
Section: Discussionsupporting
confidence: 73%
“…The rejection, hostile control, lack of warm and unpredictability that characterize the styles of parents that perpetrate maltreatment, cause their children to adopt an external locus of control, i.e., a way of thinking characterized, according to the definition provided by Rotter (1966), by attributing the responsibility for what happens in their lives to destiny and to other people (Barahal et al 1981;Ellis & Milner 1981;Serrano et al 1979). In other words, these few studies provide empirical evidence for the hypothesis that children suffering maltreatment-experiences defined as physical punishment not arising from their own behavior, psychological abuse, neglect or negligent care, exploitation and sexual abuse involving the deliberate use of threatened or actual physical strength and power by a person or group against a child and causing or having a good chance of causing actual or potential harm to the child's health, survival or dignity (ONU, 2006, p. 6)-have little confidence in the possibility that they can have an impact on their own experiences, especially the frustrating and unpleasant ones.…”
Section: Introductionmentioning
confidence: 99%
“…According to Pearce and Pezzot-Pearce (1997, p. 32), several studies have documented cognitive impairment in children with a history of maltreatment in comparison to control subjects (Barahal, Waterman, & Martin, 1981;Pezzot, 1978). The maltreated children in these studies were reported to have lower IQs than their non-maltreated peers even when the impact of neurological damage was statistically controlled.…”
Section: Trauma Within a Developmental Frameworkmentioning
confidence: 99%
“…There is increasing evidence from both clinical and nonclinical samples that adverse childhood experiences are associated with deficits in social cognitive processes such as emotion perception and theory of mind (Barahal et al 1981;Cicchetti et al 2003;Pears & Fisher, 2005;Koizumi & Takagishi, 2014). Social cognitive deficits are a core impairment of borderline personality disorder and are thought to be worsened by childhood maltreatment (Roepke et al 2013).…”
Section: Neurocognitive and Social Cognitive Impairmentmentioning
confidence: 99%